2014
DOI: 10.1093/her/cyt155
|View full text |Cite
|
Sign up to set email alerts
|

Using process data to understand outcomes in sexual health promotion: an example from a review of school-based programmes to prevent sexually transmitted infections

Abstract: This article discusses how process indicators can complement outcomes as part of a comprehensive explanatory evaluation framework, using the example of skills-based behavioural interventions to prevent sexually transmitted infections and promote sexual health among young people in schools. A systematic review was conducted, yielding 12 eligible outcome evaluations, 9 of which included a process evaluation. There were few statistically significant effects in terms of changes in sexual behaviour outcomes, but st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
(85 reference statements)
2
22
0
Order By: Relevance
“…The influence of these stakeholders has also been found in previous studies (Durlak & DuPre, 2008;Dusenbury, Brannigan, Falco, & Hansen, 2003;Paulussen, Kok, Schaalma, 1994;Shepherd et al, 2014;Wiefferink et al, 2005).…”
Section: Process Model Of Implementationsupporting
confidence: 73%
See 2 more Smart Citations
“…The influence of these stakeholders has also been found in previous studies (Durlak & DuPre, 2008;Dusenbury, Brannigan, Falco, & Hansen, 2003;Paulussen, Kok, Schaalma, 1994;Shepherd et al, 2014;Wiefferink et al, 2005).…”
Section: Process Model Of Implementationsupporting
confidence: 73%
“…This may have influenced program outcomes negatively; e.g., fear appeals are only effective when self-efficacy for the advised behavior is high (Peters, Ruiter, & Kok, 2013;Ruiter, Kessels, Peters, & Kok, 2014). Previous research has shown that teachers' incomprehension of the theoretical basis for behavior change negative influences implementation (Buston et al, 2002;Shepherd et al, 2014). To avoid 'pick and choose', a clearer justification of the exercises may enhance fidelity and completeness, for example by elaborating on methods (not) used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Features/factors influencing implementation are examined one by one Using logic models/conceptual framework Factors influencing implementation of lay health worker programmes [44] a School-based behavioural interventions to prevent sexually transmitted infections [59] Contextual features from qualitative research are integrated holistically with findings on effectiveness to develop or refine the logic model Development of framework is flexible and can incorporate stakeholder input when description in published studies is poor Analysing programme theory School feeding programmes for disadvantaged children [54] Interventions to prevent repeat teenage pregnancy [64] a Contextual features from qualitative research are integrated holistically with effectiveness findings to develop and refine programme theory Expertise in programme theory required (e.g.realist evaluation) Testing hypotheses derived using subgroup analysis Promoting positive health behaviours [27] Hypotheses from qualitative synthesis can be tested statistically Requires sufficient numbers of trials to conduct sub-group analysis Features/factors influencing implementation are examined one by one Qualitative comparative analysis.…”
Section: Juxtaposing Findings In a Matrixmentioning
confidence: 99%
“…Lack of awareness of the importance of completeness and fidelity was found to be related to incomplete program implementation of the online school-based sex education program, LLL+ for older high school students (van Lieshout et al, 2016). Previous research has shown that teachers' incomprehension of the theoretical basis for behavior change negatively influences implementation (Buston et al, 2002;Shepherd et al, 2014). Coaching can only commence when teachers develop an awareness of the need and desire to improve their performance or change the way they have been doing things at work (Parsloe & Leedham, 2009).…”
Section: Implications Recommendations and Future Researchmentioning
confidence: 99%